The Impact of Financial Crisis and ISIS on the Performance of Telecommunication Companies in Iraq “An empirical analysis of Asia and Zain Companies for the period of(2010-2018)” - Abdullah, Ranj Tahir; Majeed, Bzhar Nasradeen; Ahmed, Younis Ali (Sulaimani Journal for Humanities, 2019)
Communication plays a vital role in the human life activity. Use of various means of telecommunication now becomes an integrated part of society. Objective; the main objective of this study is to evaluate and analyse the impact of Financial Crisis and ISIS on the profitability of Asia and Zain companies. Method and Sample; to achieve this objective, statistical tools and economic analysis were applied by using annual financial statements of both companies for the period of (2010-2016 / 2010-2018). Result; study result shows a large fluctuation in the annual financial statements for both of the companies, and the level of performance was not stable from time to time. Finding; there is a strong and negative correlation between (financial crisis, ISIS) and (Asia, Zain) Co.’s profitability. Both companies have a negatives coefficient with different results. Beside this; ISIS left a negative influence on Zain by 86% on its profitability but compared to Asia cell is much smaller. Because, Zain operate in eight different countries and its market is much wider than Asia cell which operates only in Iraq. Contribution of the study; to the best knowledge of researchers, there is no current literature on this type of research. Furthermore; empirical results of the study found out how much is the effect of financial crisis and ISIS on Asia and Zain profitability, by applying data for the period of (2010-2016 / 2010-2018).Recommendation; This study’s recommendation is to diversify the companies source by diversifying the market sources and providing new services to attracting new customers.
Keywords: Financial Crisis; ISIS; Profitability; Asia Company; Zain Company; Generalized Linear Model